Investigating the usability, feasibility, and effect of a virtual reality cognitive training system on brain cancer patients with mild cognitive impairment: a quasi-experimental (single-arm) pilot study - Faiola, Anthony; Soroya, Saira (medRxiv, 2026)
Abstract (1) Background Brain cancer is the ninth leading cause of cancer death in the US, with approximately 76,000 newly diagnosed cases annually. Studies show that at time of diagnosis, up to six-months post-treatment, 50%–80% of brain cancer survivors (BCS) report cognitive dysfunction. Mild cognitive impairment (MCI) has gained increasing attention as a persistent disability experienced by up to 75% of all BCS, which affects memory, concentration, executive function, etc. Studies show cognitive training with computerized gaming as improving cognitive function for patients with stroke, dementia, and Parkinson’s. It is of significant clinical interest to develop innovative interventions that reduce MCI. Aim: To improve cognitive performance of BCS suffering with MCI by evaluating the feasibility, acceptability and effect of a Virtual Reality Cognitive Rehabilitation Training (VR-CRT) platform during four weeks of cognitive training (2) Methods We employed a quasi-experimental pretest/posttest non-randomized/non-blinded single-arm design for 4 weeks, with an experimental group (n=6, after attrition) using VR-CRT. Participants were selected based on convenience sampling using the electronic medical record to identify qualified patients, guided by inclusion/exclusion criteria. Feasibility was defined by retention as >80%, with usability testing using the System Usability Scale (SUS) and NASA-TLX surveys. The Hopkins Verbal Learning Test (HVLT), Controlled Oral Word Association (COWA) test, and Trail Making A-B (TM-A/B) test were used to measure cognitive performance, comparing baseline to post week-four. (3) Results The feasibility criteria of >80% was met. All SUS and NASA scores were in the higher index, suggesting a high degree of usability, with low workload demand. For effect, the COWA findings showed a significant improvement (41.38%), with a paired sample T-Test confirming that the participants’ COWA scores improved significantly from pre- to post-intervention ( p = 0.03), indicating enhanced verbal fluency and executive functioning after intervention. HVLT (combined) showed improvements of 18.75% for Form A and 11.32% for Form B, which also showed a significant improvement ( p = .04) in the retention discrimination index from pre- to post-test. The TM-A/B test showed an improvement (25.97%), suggesting that the participants spent less time completing both parts A and B, but was not statistically significant. (4) Conclusion This study fulfilled our aim to demonstrate modest to significant cognitive improvement using VR-CRT with brain cancer patients with MCI. Despite the small sample size, we believe the use of virtual reality will lead to important advances for patients with MCI, particularly the frontal lobe brain region, expressed in executive function.
Keywords: Cognition; Cognitive rehabilitation therapy; Cognitive training; Psychological intervention; Rehabilitation; Test (biology); Usability; Virtual reality; Workload; dept.ils

Perceptions of the Pakistani editors for open access journal publishing: a developing country’s perspective - Raza, Muhammad; Rafiq, Muhammad; Soroya, Saira (Information Development, 2025)
Objectives This study has been designed to determine Pakistani editors’ perceptions regarding the Open Access (OA) publishing practices of the Higher Education Commission (HEC)-recognized journals in Pakistan, and to assess their best OA publishing models. Methodology A structured questionnaire-based survey method of quantitative research approach was adopted to achieve the study’s objectives by collecting data from the editors of all 329 HEC-recognized journals in Pakistan. Findings This study exposed that public and teaching institutes are leading in OA journal publishing in Pakistan as compared to private and research institutes. Diamond OA, and Gold OA publishing models are popular among the respondents; however, respondents are not convinced to follow any specific OA publishing model due to their different choices. A large majority (92%) of the journals belong to the Y category (the lowest) of journals. A large majority (72%) of the journals in Pakistan is adopting the Open Journal System (OJS), and parent institutions installed web browsers. CC-BY-NC and CC-BY licenses are their favorite licenses. Significance The present study is the first comprehensive study on editors’ perceptions for OA journal publishing and is an effort to fill this gap to invigorate the scholarly literature. This study may enable the journals, editors, and publishers to follow the best OA journal publishing practices of the Pakistani journals for global OA usage of scholarly journals. The results have practical and theoretical ramifications for academic and research institutions, federal and provincial higher education commissioners, policy organizations, and parent institutions of journals.
Keywords: Computer science; Developing country; Economic growth; Economics; Library science; MEDLINE; Media studies; Open access journal; Open access publishing; Perception; Perspective (graphical); Political science; Psychology; Public relations; Publishing; Scopus; Sociology; dept.ils; peer-reviewed

Academic Integrity: Effects of Demographic Variables on Students’ Conduct - Soroya, Dr Muhammad Shahid; Hashmi, Dr Muhammad Amir; Soroya, Saira Hanif (South Asian Studies, 2020)
This study aimed to find out the effects of demographic variable i.e. gender, age, group of studies, GPA etc. on level of academic integrity among Pakistani students. The design of the study is quantitative in nature, in which the survey research method was employed to gather data from the respondents. A self-reported questionnaire was adapted on the basis of previously developed and validated questionnaire, with the consent of the authors. The developed scale was validated with the help of experts and pilot tested. Multilevel stratified convenience sampling technique was used to collect data from 4 provinces and federal area of Pakistan. The collected data was analyzed by using SPSS 16.0 version
Keywords: dept.ils

Assessing the impact of health information orientation and health information literacy on patients’ engagement with health information - Hashmi, Ferhana Saeed; Soroya, Saira Hanif; Mahmood, Khalid (Journal of Information Science, 2024)
Health information engagement can help individuals to find and use reliable sources of health information to make informed decisions about their health. This helps to improve their health outcomes and prevent unnecessary healthcare costs. Drawing upon the cognitive behavioural theory, this pilot study postulated a model to understand that the consequences of information orientation in terms of information engagement (behaviour), information literacy (cognition) and information avoidance (behaviour) in post-COVID era under health context. Furthermore, the moderation effects of health information literacy (HIL) are also calculated in managing health information avoidance beahvior. This pilot study is conducted in the context of social media exposure to health information by diabetic patients in Pakistani community. The proposed model was tested using Partial Lease Square Structural Equational Modelling (PLS-SEM). The data were collected from 166 diabetic patients (active social media users) through a survey. The study findings suggest that health information orientation on social media leads to HIL and engagement. Whereas, it has significant negative impact towards health information avoidance behaviour. Furthermore, HIL significantly increases health information engagement of diabetic patients. Also, HIL moderates the relationship between health information orientation and information engagement positively, whereas between health information orientation and health information avoidance negatively.
Keywords: dept.ils; peer-reviewed

Perceived awareness, benefits, and strategies of Pakistani editors regarding open-access journal publishing - Raza, Muhammad Zahid; Rafiq, Muhammad; Soroya, Saira Hanif (Global Knowledge, Memory and Communication, 2025)
This study aims to discover the perceived awareness, benefits and suitable strategies of the Pakistani editors of Higher Education Commission (HEC)-recognized scholarly journals regarding open-access (OA) journal publishing in Pakistan.,A structured questionnaire-based survey method of quantitative research approach was adopted to achieve the study’s objectives by collecting data from the editors of 329 HEC-recognized journals in Pakistan.,The awareness level of the respondents of the Pakistani journals is low regarding the OA concepts, resources and initiatives. The respondents of OA journals have better awareness levels than the respondents of non-OA journals. All the respondents of journals are convinced and have the view that OA journals have wider benefits for the academic community, and they need to flourish. A majority of the respondents are of the view that HEC should sponsor financial resources and technical training for OA journal publishing. The respondents of OA journals are more in favor of supporting OA journal publishing than the respondents of non-OA journals.,This study covered the lists of HEC-recognized journals of 2019. More studies may be conducted based on updated lists of HEC-recognized journals by using different research paradigms such as qualitative or pragmatic research approaches.,To the best of the authors’ knowledge, this study is the first comprehensive study on this phenomenon and is an effort to fill this gap and invigorate the scholarly literature. It may attract the attention of the policymakers, funding bodies, parent institutions of the journals and the HEC to cope with the low awareness level of the Pakistani editors regarding the OA concepts, resources and initiatives; and suitable strategies required to uplift the OA journal publishing paradigm in Pakistan.
Keywords: dept.ils; peer-reviewed

Mental Health Needs of Families of Patients in Intensive Care Units and the Role of Mobile Health: Survey Study - Faiola, Anthony; Soroya, Saira; Hao, Zhonglin; Munker, Reinhold (JMIR Formative Research, 2025)
BACKGROUND: The experiences of patients with COVID-19 and their families manifested the most devastating effects of family separation since the 1918 Spanish influenza pandemic and, with it, a call for solutions to patient isolation and its effect on family mental health. OBJECTIVE: This study examined the recent experiences of families of critical care (intensive care unit; ICU) patients related to anxiety and depression (AD), satisfaction with clinician-family communication, and counseling from mental health and social services. This study explored correlations between these factors and family interest in mobile health (mHealth) designed to improve information flow and communication from patient bedside to remote families. METHODS: Using a 36-question quantitative survey, we collected 97 responses over 6 months. We selected participants by using a convenience sampling strategy. To analyze data, we applied descriptive and inferential statistics. Participants represented a spectrum of ages, relationships to patients, and races (n=78, 80% White; n=17, 18% Black; n=2, 2% other races). Approximately 17% (n=16) of the patients were admitted for cancer, 13% (n=13) were admitted for COVID-19, and 21% (n=20) were admitted for other conditions. RESULTS: The mean score for remote families' satisfaction with patient health updates from the bedside and mental health services was 2.94 (SD 1.31), whereas that for phone communication was lower on average. The mean scores of family AD levels were elevated, and levels were higher among family members during the ICU stay than after discharge. These findings confirmed evidence of a negative correlation between transportation difficulties and satisfaction with the frequency of information provided (r=-0.284; P=.005), suggesting that, with the increase in transportation challenges, families become less satisfied with the frequency of patient health information. Family members expressed strong interest in using mHealth information and communication services (mean 8.34, SD 1.98) and having easy access to social workers to manage AD (mean 8.29, SD 2.03). Families experiencing higher levels of anxiety during patients' ICU stays had significantly greater interest in the use of an mHealth app that would provide direct access to social workers (r=0.326; P<.001), in using an mHealth videoconferencing app (r=0.319; P=.002), and in overall mHealth app use (r=0.322; P<.001). CONCLUSIONS: Family members experienced high levels of AD during patient ICU admission, as well as after discharge even though their mental health challenges were reduced. Families were highly dissatisfied with the frequency of health updates, with lower satisfaction reported among those who faced difficulties arranging transportation or lived further from the hospital. Modest but statistically significant correlations were observed between family members' reported mental health status during ICU stays and an interest in an mHealth app that could provide access to real-time bedside information, facilitate communication with bedside nurses, and support connections with social workers.
Keywords: Affect (linguistics); COVID-19; Depression (economics); Health care; ICU; Mental health; Mental illness; Receipt; communication; dept.ils; digital tools; eHealth; health equity; health technology; intensive care unit; mental health; mobile health

The influence of responsible leadership on organizational commitment: the mediating role of trust in leaders in the higher education sector - Afzal, Muhammad; Soroya, Saira; Chaudhary, Naveed; Niazi, Abdul; Ashiq, Murtaza (RADS Journal of Business Management, 2025)
Background: This study examines the impact of responsible leadership (RL) on organizational commitment by examining the mediating role of trust in the leader, as modeled by the four key dimensions of the leader's role (aggregate of virtues, principles and ethical values, stakeholder involvement, and model of the leader's role) in the context of social identity theory. Methods: We employed a quantitative research design, surveying 300 middle-level employees in grades 11 to 16 from the University of the Punjab, Lahore, Pakistan. Data collection involved a structured questionnaire covering key leadership and trust dimensions. The data analysis utilized SPSS version 22 and ADANCO version 2.2, with structural equation modeling to test hypotheses. Results: Results show that organizational commitment is significantly influenced by stakeholder involvement (0.03 p-value) and ethical principles (0.00 p-value). The aggregate of virtues (0.79 p-value) and leadership role modeling (0.26 p-value) have an insignificant direct impact. However, trust significantly mediates the relationship between organizational commitment and stakeholder involvement (0.01 p-value). Trust’s mediation effect on the link between ethical principles and organizational commitment is minimal (0.04 p-value). Conclusion: This study suggests that implementing RL practices, particularly in stakeholder involvement and ethical leadership, enhances employee commitment. Responsible leadership cultivates a positive corporate image, attracting committed stakeholders. To maximize benefits, organizations should provide senior leaders with behavioral training in RL practices, fostering an environment that boosts employee loyalty. Leadership development programs should include modules on ethical decision-making, stakeholder communication, and trust-building strategies.
Keywords: Context (archaeology); Ethical leadership; Mediation; Organizational commitment; Stakeholder; Stakeholder engagement; Stakeholder theory; Structural equation modeling; dept.ils

Investigating the Feasibility, Usability, and Efficacy of a Mobile App to Reduce Anxiety and Depression in Families of Critical Care Cancer Patients: A Quasi-Experimental Pilot Study - Faiola, Anthony; Soroya, Saira; Munker, Reinhold; Hao, Zhonglin; Lambert, Joshua (Healthcare, 2026)
Background: Cancer patients admitted to the bone marrow transplant (BMT) unit face life-threatening medical conditions. Consequently, their family members experience uncertainty, resulting in high levels of anxiety and depression (AD). Limited updates and communication from medical staff exacerbate these emotional burdens. To address these challenges, we developed a mobile health (mHealth) intervention, FamCarePlus, and evaluated its feasibility, usability, and efficacy. We hypothesized that the FamCarePlus application would demonstrate a high degree of feasibility and usability and would reduce AD compared to a control group relying solely on traditional communication through the nurses’ station. Methods: We employed a quasi-experimental pretest/posttest non-randomized, non-blinded self-report design over 3 weeks, with an experimental group (n = 10) using FamCarePlus and a control group (n = 9). We selected participants via convenience sampling using the electronic medical record to identify eligible patients and families, guided by inclusion and exclusion criteria. We used descriptive statistics and the Hospital Anxiety and Depression Scale (HADS) guidelines to analyze the data. Feasibility was defined by a retention rate > 80%, with usability testing using the System Usability Scale (SUS) and NASA Task Load Index (NASA-TLX) surveys. The HADS measured AD, comparing baseline to Week 3. Results: We met our feasibility criteria of >80%. All SUS and NASA scores were in the higher index, suggesting a significant degree of usability and low workload demand on participants. For efficacy, we compared baseline mean scores, with the experimental group reporting lower AD levels at Week 1 (41.9% and 27.8%, respectively) than the control group (55.2% and 34.2%, respectively). From Week 1 to Week 3, the percentage change showed an 8.6% decrease in anxiety in the experimental group, compared to a 12.8% decrease in anxiety in the control group. These results were consistent when analyzed according to HADS guidelines. Conclusions: The findings of this study provide preliminary evidence that the FamCarePlus intervention is feasible and usable, while also demonstrating that its use may be associated with a sustained reduction in AD levels among family members of patients admitted to the BMT unit. These outcomes underscore the potential of digital interventions to address disparities in patient health information access and psychosocial support.
Keywords: Anxiety; Depression (economics); Descriptive statistics; Hospital Anxiety and Depression Scale; System usability scale; Usability; Workload; anxiety; cancer; depression; dept.ils; families; intensive care unit; mHealth

From information seeking to information avoidance: Understanding the health information behavior during a global health crisis - Soroya, Saira Hanif; Farooq, Ali; Mahmood, Khalid; Isoaho, Jouni; Zara, Shan-e (Information Processing & Management, 2021)
Individuals seek information for informed decision-making, and they consult a variety of information sources nowadays. However, studies show that information from multiple sources can lead to information overload, which then creates negative psychological and behavioral responses. Drawing on the Stimulus-Organism-Response (S-O-R) framework, we propose a model to understand the effect of information seeking, information sources, and information overload (Stimuli) on information anxiety (psychological organism), and consequent behavioral response, information avoidance during the global health crisis (COVID-19). The proposed model was tested using partial least square structural equation modeling (PLS-SEM) for which data were collected from 321 Finnish adults using an online survey. People found to seek information from traditional sources such as mass media, print media, and online sources such as official websites and websites of newspapers and forums. Social media and personal networks were not the preferred sources. On the other hand, among different information sources, social media exposure has a significant relationship with information overload as well as information anxiety. Besides, information overload also predicted information anxiety, which further resulted in information avoidance.
Keywords: COVID-19; Information anxiety; Information avoidance; Information overload; Information seeking; dept.ils